342 The effects of extended colostrum feeding on gastrointestinal tract growth of the neonatal dairy calf. (7th December 2018) - Pyo, J; Pletts, S; Romao, J; Inabu, Y; He, Z; Haines, D; Sugino, T; Guan, L; Steele, M
Abstract: Colostrum is rich with bioactive molecules, such as hormones, that may stimulate the growth of the gastrointestinal tract (GIT) of the neonatal calf. However, there is limited information regarding the effect of colostrum feeding strategies on GIT growth and development, especially at varying durations and amounts of colostrum. Therefore, the objective of this study was to determine the effect of extended colostrum feeding duration on the gastrointestinal tract (GIT) growth of neonatal dairy calf. Twenty four Holstein bull calves were fed colostrum at 7.5% of BW 2 h postnatal and randomly assigned (n = 8/treatment) to either colostrum (COL), 1:1 colostrum:milk (MIX), or whole milk (MILK). Treatment meal was fed at 5% of BW every 12 h, beginning 12 h postnatal. Sequential blood samples were collected using a jugular catheter and analyzed for the concentration of plasma glucagon-like peptide 2 (GLP-2). Calves were euthanized on d 3 and tissues were collected from duodenum, proximal and distal jejunum, and ileum for histology. For statistical analysis a three-way ANOVA proc MIXED model in SAS program was used ( P < 0.05). Villi length was shorter in MILK calves (297.25 µm ± 7.16) than MIX (472.54 µm ± 11.81) and COL (449.76 µm ± 22.86) calves in the jejunum and ileum. The blood concentration of GLP-2 indicated that MIX and COL calves had the larger total area under the curve (2171.83ng/mL×h and 2157.73ng/mL×h; MIX and COL, respectively) compared to calves fed MILK (1806.43 ng/mL×h). In closing, the results suggest that extending colostrum feeding for 3 d postnatal has growth promoting effects in the neonatal GIT that may be beneficial for nutrient absorption and gut health in the neonatal dairy calf.